Kajian Kesiapan Investasi TIK dengan Pendekatan Integratif (Studi Kasus: SMAN 01 Sanggau) - Tjiptabudi, Fransiskus Mario Hartono; Setiawati, Donna; Ndaumanu, Ricky Imanuel (JITU, 2025)
The high cost of ICT investment is often an obstacle to ICT implementation, especially for educational institutions with limited budgets. Without analysis, the risk of budget waste and incompatibility with the real needs of the institution becomes higher. This study aims to assess the readiness of information and communication technology (ICT) investment using an integrative approach that combines Cost-Benefit Analysis (CBA), Technology-Organisation-Environment (TOE) Framework, and OODA Loop. This approach is designed to provide a comprehensive evaluation of economic, technological, organisational, and decision-making dynamics in ICT investment. The research method uses a qualitative approach with data collection through observation, interviews, and documentation studies. The analysis is carried out by integrating the results of CBA to assess the feasibility of investment, the TOE Framework to identify factors influencing technology adoption, and the OODA Loop to understand the iterative and adaptive decision-making process. The research findings indicate that based on the CBA analysis, the ICT investment in the form of developing and implementing an e-learning system at SMAN 01 Sanggau is highly feasible to execute. However, from the TOE Framework perspective, the organisation's readiness to adopt the e-learning system is still partial with some shortcomings. From the OODA Loop perspective, the investment is deemed feasible after considering: financial calculations showing benefits through metrics such as NPV, ROI, and PP, non-financial benefits such as improved access to learning and educational quality, and proactive risk mitigation against technical, financial, and operational challenges.